Determination of acrylamide levels in potato crisps and other snacks and exposure risk assessment through a Margin of Exposure approach. (October 2017) - Esposito, Francesco; Nardone, Antonio; Fasano, Evelina; Triassi, Maria; Cirillo, Teresa
Abstract: Potato crisps, corn-based extruded snacks and other savoury snacks are very popular products especially among younger generations. These products could be a potential source of acrylamide (AA), a toxic compound which could develop during frying and baking processes. The purpose of this study was the assessment of the dietary intake to AA across six groups of consumers divided according to age through the consumption of potato crisps and other snacks, in order to eventually evaluate the margin of exposure (MOE) related to neurotoxic and carcinogenic critical endpoints. Different brands of potato crisps and other popular snacks were analyzed through a matrix solid-phase dispersion method followed by a bromination step and GC-MS quantification. The concentration of detected AA ranged from 21 to 3444 ng g − 1 and the highest level occurred in potato crisps samples which showed a median value of 968 ng g − 1 . The risk characterization through MOE assessment revealed that five out of six consumers groups showed higher exposure values associated with an augmented carcinogenic risk Highlights: 75 samples consisting of potato crisps and cocktail snacks were analyzed for the occurrence of acrylamide. The concentration of acrylamide in potato crisp was higher than in other food categories. A risk characterization was performed through a Margin of Exposure (MOE) approach. Some groups showed a not negligible MOE for carcinogenic endpoints, especially as regards potato crisps.